1990
DOI: 10.1159/000118711
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Psychotropic Drug Consumption Related to Psychological Distress in the Elderly: Hospitalized vs. Nonhospitalized

Abstract: The use of psychotropic drugs in general has become more extended in the past 20 years. The elderly, particularly geriatric inpatients, are the group with the highest consumption. The aim of the present study was to evaluate in two groups of elderly, hospitalized patients (H) vs. nonhospitalized subjects (nH), psychotropic drug consumption related to psychological distress. This was carried out in a total 238 subjects aged above 65 years (112 geriatric inpatients and 126 interviewed in social welfare centers).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…The lower use of psychotropic drugs can be further evidenced by the use of specifi c therapeutic classes of psychotropic drugs. For example, in the present study the prevalence of benzodiazepine use was 3.7 % , as opposed to previously reported prevalence estimates of 14.9 % in France [39] , 17.3 % in Ireland [27] , 13.7 % in Spain [4] and 10.8 % in the UK [49] . The same applies to the use of antidepressants, anxiolytics, sedatives / hypnotics and neuroleptics as reported from other European countries [20,37,41,52] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lower use of psychotropic drugs can be further evidenced by the use of specifi c therapeutic classes of psychotropic drugs. For example, in the present study the prevalence of benzodiazepine use was 3.7 % , as opposed to previously reported prevalence estimates of 14.9 % in France [39] , 17.3 % in Ireland [27] , 13.7 % in Spain [4] and 10.8 % in the UK [49] . The same applies to the use of antidepressants, anxiolytics, sedatives / hypnotics and neuroleptics as reported from other European countries [20,37,41,52] .…”
Section: Discussioncontrasting
confidence: 99%
“…Although no confi rmatory nationally representative data exist, it seems likely that the slightly lower use of psychotropic drugs in the general population may extend to Germany ' s older population. The prevalence of use of all psychotropic drugs among community-dwelling elderly adults has been reported as being 22.1 % in France [39] , 21.9 % in Ireland [27] , 16 % in Spain [4] , 37 % in Sweden [19] , 25 % in Finland [32] and 18.8 % in the ESEMeD study for the old population subgroup [2] , compares with 20.1 % for the use of all psychotropic drugs and 14.1 % for synthetic psychotropic drug use in our study, and 12.2 % in an earlier regional study conducted in the south of Germany [53] . A much higher prevalence (29.8 % ) of psychotropic drug use has been reported in a regional study among Berlin ' s elderly aged between 70 and 100 + , years which can largely be explained by the disproportionate over-sampling of the very old and of men [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Community surveys in the United States (Swartz et al 1991) and Western Europe (Fichter et al 1989;Pakesch et al 1989;Vazquez-Barquero et al 1989) have found significant positive correlations between benzodiazepine use and psychiatric disturbance as measured using standard rating instruments. Among patients of general practices, those who had receipted prescriptions for benzodiazepines scored significantly higher on such ratings than matched controls who had not received such prescriptions (Salinsky and Dore 1987;Gen6e-Badia et al 1988) Other studies of general medical patients in the United States (Haskell et al 1986;Ried et al 1990) and Western Europe (Magni et al 1986;Bellantuono et al 1989;Antonijoan et al 1990) also showed that benzodiazepine users were distinguished by significant psychiatric morbidity; some of these (Magni et aI. 1986;Antonijoan et al 1990;Ried et al 1990) specifically studied elderly patient populations.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Despite the abundance of studies on the interaction between mental health and stress-related factors such as life events (i.e., major events such as loss of a spouse or a serious illness) or social support (Flannery & Wieman, 1989;Swindle, Cronkite, & Moos, 1989), little is known of this relationship when prescribed psychoactive drug use is introduced into the equation. When users are simply contrasted with nonusers on various chosen health and psychosocial variables (Antonijoan, Barbanoj, Torrent, & Jane, 1990;Pariente, Lepine, & Lellouch, 1992;Pérodeau, Jomphe Hill, Hay-Paquin, & Amyot, 1996;Weyerer & Dilling, 1991), they invariably appear under a more negative light than the latter group. However, when associative patterns between variables are examined, results are more ambiguous.…”
mentioning
confidence: 99%